Implementasi Kebijakan Kredit Usaha Rakyat Guna Mendorong Peningkatan UMKM di Kantor Cabang Non Metro Bank BRI Jakarta 3 - Laras Ayu Maulida Zahra (MES Management Journal, 2024)
Kredit Usaha Rakyat (KUR) is a government policy in Indonesia initiated in 2007. KUR provides financial assistance to micro, small, and medium enterprises (MSMEs) under specific conditions and terms. The general aim of KUR is to support the Indonesian community in developing their MSMEs to progress continuously. It not only aids the community in business ventures but also contributes to Indonesia's GDP due to the significant potential of MSMEs in boosting the national economy. This study aims to understand how the implementation of the Kredit Usaha Rakyat (KUR) operates in non-metro branch offices of Bank BRI. The research employs a qualitative method involving interviews with employees at the Jakarta 3 regional office of Bank BRI, revealing that the policy's implementation has been effective.